The effect of microwave hydrothermal treatment on the combustion behavior of sewage sludge - Jin, Zechen; Zhang, Qian; Qiu, Fengxiang; Hu, Weijie; Feng, Yuheng; Zhang, Shuping (Frontiers in Environmental Science, 2022)
In this study, microwave hydrothermal treatment of sewage sludge was conducted and the combustion behavior of the product (MTC) was compared with dried raw sludge (DS) and the traditional hydrothermally treated sludge by electric heating (ETC). Compared with MTS, the volatile retention rate of HTS was raised by 51.2%, while their moisture removal rates by centrifugation were very close. The kinetic parameters were determined from TG analysis. it was found that the activation energy of combustion was reduced from 78.63kJ/mol of DS for ETC to 84.66 kJ/mol. For MTC, the activation energy was abit decreased (78.14 kJ/mol). In addition, the highest average weight loss rate (0.49%/min) in combustion was also found for MTC. The evolution of different gaseous products was obtained by FTIR analyzer combined with TG. The results indicated that in devolatilization process, the emission of NH3, which is the main precursor of NOx in combustion, was postulated to higher temperature for MTC. In conclusion, MTC has a better combustion performance and a close dewaterability compared with to ETC. This study provided a new choice for the pre-treatment method of sewage sludge before combustion.